2004
DOI: 10.3168/jds.s0022-0302(04)73137-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Milk Powders in Milk Chocolate

Abstract: The physical characteristics of milk powders used in chocolate can have significant impact on the processing conditions needed to make that chocolate and the physical and organoleptic properties of the finished product. Four milk powders with different particle characteristics (size, shape, density) and "free" milk fat levels (easily extracted with organic solvent) were evaluated for their effect on the processing conditions and characteristics of chocolates in which they were used. Many aspects of chocolate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 9 publications
4
66
0
3
Order By: Relevance
“…For semi-solid fat products such as chocolates or cocoa butter, the rheological properties of fats are the result of a combined effect of the SFC (solid fat content) and the three-dimensional colloidal fat crystal network micro-structure, including the shape, size, spatial distribution pattern of the crystals [17,21,37,42,56,57,79,80,82]. Cocoa butter can crystallise in a number of polymorphic forms depending on the triglyceride composition [1].…”
Section: Crystallisation Of Fatsmentioning
confidence: 99%
“…For semi-solid fat products such as chocolates or cocoa butter, the rheological properties of fats are the result of a combined effect of the SFC (solid fat content) and the three-dimensional colloidal fat crystal network micro-structure, including the shape, size, spatial distribution pattern of the crystals [17,21,37,42,56,57,79,80,82]. Cocoa butter can crystallise in a number of polymorphic forms depending on the triglyceride composition [1].…”
Section: Crystallisation Of Fatsmentioning
confidence: 99%
“…Many factors influence the formation of the flavor of chocolate products. The flavour of milk chocolate can be affected by the quality of the raw materials used such as the quality of milk powder that were used in the milk chocolate's ingredient (Liang and Hartel 2004). The more cinnamon addition in milk chocolate decreases panelists acceptability.…”
Section: Taste Attributesmentioning
confidence: 99%
“…The effect of milk powder addition to physical and sensory properties of milk chocolate has been reported by Liang and Hartel (2004). Meanwhile Aidoo et al (2010) and Glicerina et al (2015) reported the effect of raw materials substitution and the effect of manufacturing process on the quality attributes of milk chocolate, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature was first focused on the free fat content and its negative effects on powder physical properties, such as rehydration, flowability and oxidation stability [5,7,14,18]. Conversely, in the case of chocolate processing, a high free fat content is required to lower the viscosity of the mass [2,19,27]. The investigation of the surface composition was recently achieved by Fäldt et al [11], who adapted X-ray photoelectron spectroscopy (XPS) to the study of dairy powders.…”
Section: Introductionmentioning
confidence: 99%